Multifractal models in finance: Their origin, properties, and applications - Mawuli Segnon; Thomas Lux (Kiel Institute for the World Economy (IfW), 2013)
This chapter provides an overview over the recently developed so called multifractal (MF) approach for modeling and forecasting volatility. We outline the genesis of this approach from similar models of turbulent flows in statistical physics and provide details on different specifications of multifractal time series models in finance, available methods for their estimation, and the current state of their empirical applications.
Keywords: C20; F37; G15; G17; 330; multifractal processes; random measures; stochastic volatility; forecasting